Analysis of Factors Associated with Work Performance of Inpatient Nurse in Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia - Andreza; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Hospital is a health service institution that provides complete individual health services. The success of a hospital is determined by the performance of its employees. To improve the quality of health services, nurses who are reliable and have good performance are needed. Good nurse performance is expected to have a positive impact on organizational performance, in this case, the hospital itself. This study aims to identify and analyze the factors that influence nurse performance. Subjects and Methodes: The study design used descriptive analytic using a cross sectional approach. Study location at Dr. Wahidin Sudirohusodo Central General Hospital Makassar in March 2023. Subjects were 272 nurses in the Inpatient Room. Quantitative data analysis, namely univariate, bivariate and path analysis. Results: Motivation affects nurse performance (b = 0.63; 95% CI = 0.55 to 0.72; p < 0.001). Job satisfaction affects nurse performance (b = 0.20; 95% CI = 0.30 to 0.30; p < 0.001). Discipline affects nurse performance (b = 0.11; 95% CI = 0.01 to 0.23; p = 0.049). Motivation has an effect on discipline (b = 0.46; 95% CI = 0.39 to 0.53; p < 0.001). Job satisfaction affects discipline (b = 0.30; 95% CI = 0.21 to 0.39; p < 0.001). Leadership effect on discipline (b = 0.27; 95% CI = 0.21 to 0.35; p < 0.001). Motivation has an effect on job satisfaction (b = 0.31; 95% CI = 0.24 to 0.38; p < 0.001). Stress has an effect on job satisfaction (b = 0.06; 95% CI = 0.01 to 0.12; p = 0.036). Leadership influences job satisfaction (b = 0.21; 95% CI = 0.15 to 0.29; p < 0.001). Work environment influences job satisfaction (b = 0.52; 95% CI = 0.45 to 0.59; p < 0.001). Conclusion: Nurse performance is influenced by motivation, work discipline, work stress, job satisfaction, leadership, and work environment. Keywords: Motivation, discipline, work stress, job satisfaction, leadership, work environment, nurse performance Correspondence: Andreza. Master’s Program in Public Health, Graduate School, Universitas Sebelas Maret. Jl Ir. Sutami 36 A Kentingan Surakarta, Jawa Tengah, Indonesia. Email : Andrezafauzialghifary@gmail.com. Mobile: 085299015320.